Seroepidemiology of Reovirus in Healthy Dogs in Six Prefectures in Japan - HWANG, Chung Chew; MOCHIZUKI, Masami; MAEDA, Ken; OKUDA, Masaru; MIZUNO, Takuya (Journal of Veterinary Medical Science, 2014)
Reovirus infection is common in mammals. However, seroepidemiological data of reovirus neutralizing antibodies are limited in dogs. In this study, sera of 65 healthy dogs from six prefectures across Japan were tested for neutralizing antibodies against reovirus serotype 1 strain Lang (T1L), serotype 2 strain Amy (T2A) and serotype 3 strain Dearing (T3D) using plaque reduction neutralization test (PRNT). Seropositivity against reovirus T1L, T2A and T3D was 53.85%, 33.85% and 46.15%, respectively. Distribution of reovirus seropositive samples displayed no distinguishable geographical pattern. However, reovirus seropositivity increased with age and in dogs housed outdoor. Co-infection of multiple reovirus serotypes in dogs was also detected. These data will provide valuable insights towards the usage of reovirus in oncolytic virotherapy in canine cancers.